KAJIAN PENGARUH PERUBAHAN TATAGUNA LAHAN TERHADAP FLUKTUASI DEBIT DAS JANGKOK PROVINSI NUSA TENGGARA BARAT - , I Ketut Darmawan, Ir. Joko Sujono, M.Eng., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
A change in land use will affect characteristics of the watershed (DAS), and also its hydrological system. The change in the hydrological system also impacts on the availability of water in the watershed. These changes include surface runoff, interflow, and groundwater flow. The analysis of fluctuation in the watershed was conducted based on the effect of changing land use in different years, in rainy conditions of 2000 and 2006, by using SK. Ministry of Forestry of 2001 and software modeling of HEC- HMS (Hydrologic Modeling System). The model was used to estimate the flow of a rain catchment system, especially on low flow. The research was carried out through calibration process based on rainfall data, discharge, and evapotranspiration of same year and also reviewing some representative parameters for the watershed. The further process is simulations based on these parameters with the same rainy conditions scenario toward the different land uses. This process is tailored to research area divided into three subwatersheds e.g., Aiknyet, Keling and Bugbug that giving the quantities of surface water and soil flow. Overall, the average value for the Jangkok watershed KRS in ten years (years 2000-2009) on rainy season is 67 that classified intermediate and on dry season is 18 that considering SK.Men.Hut.tahun 2001 classified as good enough. The coefficient of variation at Jangkok watershed tends to increase as yearly. Besides affected by the rainfall it also influenced by the presence of ponds. In dry season the water flowed to another place resulting the discharge at the control station reduced, and acquisition of the variation coefficient to increase. The condition of Jangkok watershed in 2006 based on the standard of evaluation of the Minister of Forestry, has IPL value by 65% and the condition of Jangkok watershed considering the standard evaluation in terms of land use index (IPL) classified as intermediate. The analysis result revealed a change in flow rate due to changes in watershed land use. Comparison of changes in discharge decreased from 2000 to 2006 that is in the dry season the flow reduction for sub watershed Aiknyet -25.12%, Sub Keling at -22.58% DAS and the DAS Sub Bugbug of -42.65%. The decrease is caused by changing flow rates of land-use forest land into plantations and shrubs. The projection in 2014, considering its widespread changes in forest stands, will predict globally a decline in the annual groundwater flow entering the river system of Aiknyet sub watershed -49.15%, Keling sub watershed -35.42%, and Bugbug sub watershed -49.10%.